The right to development and sustainable use of the environment: the need for ecological balance - Maidin, Ainul Jaria (American-Eurasian Network for Scientific Information (AENSI), Jordan, 2011)
The advent of industrial revolution marks the beginning of activities of man in relation with his environment. Thus, man began to strive for development at the expense of environmental degradation. The right to development further compounds this as people started all sorts of development on without regard to its environmental impacts. This also led to the concept of sustainable development of the environment. There is therefore the need to balance these two sides of a coin. This paper makes a critical exposition the concept of a right to development and the principle of sustainable development as it affects the environment. It also seeks show how to maintain an ecological balance between development and sustainability of the environment. The aim of the paper is to create a framework for friendly and developed environment which guarantees the rights of the future generation. It hypothesises that where ecological balance is maintained; it will lead to development without jeopardizing the interest of future generation. International legal instruments are made use of in this paper to analyse the issues.